2019
DOI: 10.1136/bmjopen-2018-025401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a risk-stratified intervention strategy on surgical complications: experience from a multicentre prospective study in China

Abstract: ObjectivesTo develop a risk-stratified intervention strategy and evaluate its effect on reducing surgical complications.DesignA multicentre prospective study with preintervention and postintervention stages: period I (January to June 2015) to develop the intervention strategy and period II (January to June 2016) to evaluate its effectiveness.SettingFour academic/teaching hospitals representing major Chinese administrative and economic regions.ParticipantsAll surgical (elective and emergent) inpatients aged ≥14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Several studies have proved an association between higher BMI and postoperative infection [ 24 , 25 ]. Xiaochu Yu et al [ 24 ] also found that obese patients undergoing acetabular fracture surgery had an increased rate of wound infection compared with non-obese patients. Patients with BMI over 28 kg/m 2 were five times more likely to have a wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proved an association between higher BMI and postoperative infection [ 24 , 25 ]. Xiaochu Yu et al [ 24 ] also found that obese patients undergoing acetabular fracture surgery had an increased rate of wound infection compared with non-obese patients. Patients with BMI over 28 kg/m 2 were five times more likely to have a wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…For comparability, the complications were similar to those used in RCTs [22,23]. The de nitions of these complications are detailed in a previous report [24]. To have a su cient sample size for the stability of the results, we de ned a composite outcome by combining death and all complications.…”
Section: Exposure and Outcomesmentioning
confidence: 99%